(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
Employee motivation and training programs are widely recognized as critical factors that influence organizational productivity. This study investigates the relationship between employee motivation, training initiatives, and productivity in organizations operating in Uzbekistan. Using a mixed-method approach combining surveys and secondary data, the study reveals that both intrinsic and extrinsic motivational factors, coupled with structured training programs, significantly enhance employee performance and overall organizational productivity